ANALISIS KEANDALAN SISTEM KELEMBAGAAN BERBASIS NELAYAN TERHADAP RISIKO PEMANFAATAAN BERSAMA RUANG LAUT DI KAWASAN STRATEGIS PARIWISATA - IDA AYU OKA SUWATI SIDEMAN; NYOMAN BUDIARTHA RM; IDA BAGUS PUTU ADNYANA; NGAKAN KETUT ACWIN DWIJENDRA (GANEC SWARA, 2021)
The determination of the National Tourism Strategic Area (KSPN) in the Gili Air, Gili Meno and Gili Trawangan areas in the Gili Indah area, North Lombok district, NTB makes the ports in these areas have the function of industrial synergy (in this case the tourism industry) in addition to their main function as nodes transportation. This affects the movement in the marine space of the Gili Indah area. Adaptation of all movements that are needed to achieve the sea space is a risk that arises. One of the risks of movement according to previous research is the economic sector. This study analyzes the institutional system based on fisheries and marine tourism as a synergy to support the goals of KSPN. This research was conducted by analyzing the priority hierarchy in which risk screening was carried out using a qualitative method in an ontological perspective. The results showed that the most risky element was the management of the impact of production waste with a value of 0.89, which caused the 'nothing to do' level to be 0.81. This is because the third dyke does not have a Final Processing Site (TPS) and a Wastewater Treatment Plant (IPAL). In general, by 'taking an action' in the form of sanitation and capacity building of traditional fishermen. resulting in a program value of 90%